Pelatihan Eco-Enzyme untuk Pencegahan Blooming Eceng Gondok di Sungai Bengawan Solo - Ardana Putri Farahdiansari; Laily Agustina Rahmawati; Mrabawani Insan Rendra; Muhammad Bakhru Tohir; Aulia Dinar Rosyadin (Abdimas Universal, 2024)
The Bengawan Solo River has a large and important role in the lives of the people in its flow from Central Java to East Java. However, it turns out that community activities often have an impact on Bengawan Solo, especially regarding pollution and environmental damage. One of the worrying phenomena is the blooming of Water Hyacinth, which occurred due to a long dry season, causing high concentrations of organic waste in river waters at the end of 2023. Increased human activities, including household activities, have resulted in higher amounts of waste being produced from time to time. The large amount of waste entering the river certainly causes an increase in river nutrients, thereby fertilizing Water Hyacinth along Bengawan Solo, including in the Kuncen village area, Padangan sub-district. So that household waste does not cause problems for the environment and health, it is necessary to carry out further processing of the waste. One type of household waste, namely vegetable waste, can be a source of alternative raw materials to be used as eco-enzyme products. LPPM Bojonegoro University in collaboration with Jasa Tirta I carries out community assistance activities by providing education and campaigning for awareness of the importance of maintaining the environmental condition of the Bengawan Solo river. This education and campaign is also aimed at minimizing waste from households, especially organic waste, so that there is no accumulation of nutrients that cause water hyacinth blooms. By implementing this community service, it was found that housewives' insight into managing household waste, especially vegetable scraps, increased, so that the waste could be managed into eco enzymes which are beneficial for the environment.